Making Lithuanian Families Across Borders: Conceptual Frames and Empirical Evidence - Juozeliūnienė, Irena; Seymour, Julie (Vilnius University Open Series, 2020)
This edited collection opens the door to understanding the representations and experiences of Lithuanian migrant families. The authors aim to highlight the most recent theoretical frames through which to understand the personal lives, family practices of migrants, and the ways family relationships could be perceived as ‘troubled’. The authors test and extend these ideas about family life with a focus on gender and intergenerational issues in the context of Lithuanian families across borders.
Keywords: none